1964
DOI: 10.1177/002242786400100202
|View full text |Cite
|
Sign up to set email alerts
|

Some Correlates of Staff Ideology in the Prison

Abstract: In 1962, a group of U.C.L.A. sociologists conducted a survey of staff members of the California Department of Corrections. Data were gathered on staff attitudes in relation to job and insti tutional variation. Factor analytic reduction of 28 items measur ing authoritarian orientation, preference on severity of penalties, optimism or pessimism regarding treatment outcome, and pre ferred social distance vis-à-vis parolees, resulted in measures of authoritarianism, pessimism, social distance, and recommenda tions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Interestingly, Farkas (1999) reported that female jail officers were more likely to hold a punitive orientation in comparison to male officers. Findings from other studies suggest that there is no relationship between gender and support for treatment and/or punishment (Arthur, 1994;Burton, Ju, Dunaway, & Wolfe, 1991;Cullen, Lutze, Link, & Wolfe, 1989;Jurik & Halemba, 1984;Kasselbaum, Ward, & Wilner, 1964;Leiber, 2000;Leiber & Woodrick, 1997;Robinson et al, 1993;Van Voorhis, Cullen, Link, & Wolfe, 1991;Whitehead & Lindquist, 1989;Whitehead, Lindquist, & Klofas, 1987).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Farkas (1999) reported that female jail officers were more likely to hold a punitive orientation in comparison to male officers. Findings from other studies suggest that there is no relationship between gender and support for treatment and/or punishment (Arthur, 1994;Burton, Ju, Dunaway, & Wolfe, 1991;Cullen, Lutze, Link, & Wolfe, 1989;Jurik & Halemba, 1984;Kasselbaum, Ward, & Wilner, 1964;Leiber, 2000;Leiber & Woodrick, 1997;Robinson et al, 1993;Van Voorhis, Cullen, Link, & Wolfe, 1991;Whitehead & Lindquist, 1989;Whitehead, Lindquist, & Klofas, 1987).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Education has been linked with greater support for rehabilitation, a more positive view of inmates, and inversely linked with support for punishment (Arthur, 1994;Burton et al, 1991;Jurik, Halemba, Musheno, & Boyle, 1987;Kasselbaum et al, 1964;Poole & Regoli, 1980;Robinson et al, 1993;Teske & Williamson, 1979). Other research findings, however, suggest that there is no relationship Crouch & Alpert, 1982;Cullen et al, 1989Cullen et al, , 1993Farkas, 1999;Gordon, 1999;Gordon, 2006;Jurik, 1985;Leiber & Woodrick, 1997;Paboojian & Teske, 1997;Shamir & Drory, 1981;Sundt & Cullen, 2002;Van Voorhis et al, 1991;Walters, 1995;Whitehead & Lindquist, 1989).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This dual emphasis o n custody and treatment often results in two clearly delineated, mutually antagonistic staff groupings (Clemmer, 1940;Wheeler, 1961). Conflicts between custody and treatment staff arise from their different roles (Weber, 1957), the priorities they assign to organizational goals (Piliavin and Vadum, 1968;Ohlin, 1956; Kassebaum et al, 1964), and the differing views which emanate from role expectations (Hedblom, 1963;Brown et al, 1971; Williams and Thomas, 1976).…”
Section: Organizational Goals and Role Conflictmentioning
confidence: 99%
“…A historical image of the correctional officer is that of an uncaring, punitive, and security-oriented individual (Duffee, 1974;Kassebaum, Ward, & Wilner, 1964;Poole & Regoli, 1980). Yet scholarship conducted in prisons argues that these images are not based on reality, as correctional officers embrace treatment as well as custody as a goal of corrections, and often are professionally oriented Whitehead, Linquist, & Klofas, 1987).…”
Section: Prior Research Professional Orientation Of Correctional Officersmentioning
confidence: 99%